Transgender Children: From Controvery to Dialogue. Issue 1 (31st December 2022) - Osserman, Jordan; Wallerstein, Hannah
ABSTRACT: This paper introduces the topic and unique format of the section that follows, on psychoanalytic work with transgender children. We first review the apparent impasse that characterizes our field regarding clinical work with gender diverse kids, as well as the reasons we pursued a live dialog to push thinking forward. Then, we outline the structure of the entire section, in which four contributors offer short essays, followed by a transcribed and edited version of the dialog we facilitated, which uses these essays as a starting point. We conclude with reflections on some of the themes that arise in the dialog, and implications for all of us who work in the arena of gender and young people.